Sirolimus: A Rescue Drug to Control Complications of Extensive Venous Malformation - Mohamed Aly Abdelbaky; Iman Ahmed Ragab; Amr AbdelHamid AbouZeid; Shaimaa Abdelsattar Mohammad; Mohamed Moussa Dahab; Mohammed Elsherbeny; Hatem Abdelkader Safaan (Georg Thieme Verlag KG, 2020)
Venous malformations represent a major sector of vascular anomalies. Most cases are asymptomatic or subclinical; however, large extensive lesions can cause severe disability and sometimes mortality. In this report, we present a successful case of sirolimus treatment in managing an extensive venous malformation in the pelvis of a 21-month-old boy who presented with life-threatening complications. With a history dating since the day 2 of life, the patient suffered from chronic bleeding due to scrotal skin ulcerations, in addition to recurrent attacks of severe bleeding per rectum necessitating hospital admission and blood transfusion (three attacks since the age of 7 months). Pelvic magnetic resonance image showed the typical findings of extensive venous malformation involving the pelvis, perineum, scrotum, and extending to the gluteal region. The lesion was seen totally encasing the anorectum with marked thickening of their walls almost occluding their lumen. Oral sirolimus (2 mg/m2) was started with a target blood trough level of 5 to 10 ng/mL. Over a follow-up period of 5 months, there was obvious clinical improvement that included healing of skin lesions (scrotal ulcer) with complete re-epithelialization, absence of bleeding per rectum with improvement of constipation, and rise of hemoglobin level from 7.5 to 11.5 g/dL.